E-counselling: the intention, motivation and deterrent among school counsellors - Lai, Wei Foon; Zainudin, Zaida Nor; Mohamad Yusop, Yusni; Wan Othman, Wan Norhayati (Horizon Research, 2020)
Internet technologies are rapidly changing our lives, so school counsellors are now facing challenges to provide innovative ways in order to support students in their preferred communication mode. This study sought to understand the perception of school counsellors towards e-counselling on (1) their intention to use e-counselling; (2) the motivators for them to offer e-counselling; and (3) the deterrent factors from offering e-counselling. 66 school counsellors completed this online survey. All had online communication experience with their students. Counsellors showed positive intention to apply e-counselling in schools only when e-counselling facilities were provided. Lack of competence in technical skill seemed to outweigh their intention to use e-counselling. Appropriate professional development, technical training and the practice-based research in school comparing effectiveness of e-counselling and face-to-face were the leading three motivators for school counsellors to use e-counselling. Fear of miscommunication due to unfamiliar online language, lack of professional development and technical skill training, lacks of technical resources were the key deterrents that deter their intention to offer to e-counselling. The major contribution from this study indicated that school counsellors were receptive to offer e-counselling in school with the conditions that they were given adequate and appropriate professional development, technical trainings and e-counselling facilities.